Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

Earn While you Learn Sutton : A CEDEC Collaboration Story - Community Economic Development and Employability Corporation (CEDEC)
Tourism is a major economic driver in the Sutton area, however, labour shortages are hampering growth. Through innovative skills training, tourism sector employers are attracting new talent and through upskilling they are retaining and promoting their existing workforce to take on new responsibilities and secure year-round employment.